(untitled) (EAAE Annual Conference Proceedings, 2023)
The UN estimates that 68% of the world population will live in urban areas by 2050. This, combined with the overall population growth could add 2.5 billion people to already overcrowded cities. Prompting many countries to face challenges in meeting the needs of their growing urban populations. Reconciling urban sprawl, verticality and the lack of housing will force us to adapt to greater density and new housing typologies. With more and more people moving into cities, understanding the key trends in urbanization will be crucial in implementing the Sustainable Development goals proposed by the UN.